Avaliação da prevalência das doenças peri-implantares e do sucesso e sobrevivência de implantes osseointegrados com 8 a 10 anos de função - Marcantonio, Claudio [UNESP] (2014)
The aim of the present study was to verify the long-term success and survival rates of osseointegrated dental implants, as well to determine the prevalence of peri-implant disease, and to identify potential risk factors associated to the occurrence of peri-implantitis. The sample was comprised of 50 patients who had their implant-supported rehabilitation concluded between the years of 2003 and 2005. Evaluations included the gathering of demographic, systemic and behavioral information, as well as radiographic and clinical records for the assessment of periodontal and peri-implant conditions. Multivariate analysis was employed to identify potential risk factors related to the occurrence of peri-implantitis. A total of 211 implants were installed, out of which 5 were lost and 9 were submerged, that is, nonfunctioning. Thus, 197 implants in 48 patients were clinically evaluated. The presence of osteoporosis (OR = 2,87) and the presence of full-mouth BOP scores ≥ 30% of sites (OR = 8,03) were variables significantly associated with a higher occurrence of peri-implantitis, among the subjects. At the implant level, the presence of visible plaque (OR = 4.45) and the presence of sites with probing depth (PD) ≥ 4 mm (OR = 4.47) were variables significantly associated with a higher occurrence of peri-implantitis. Mucositis prevalence was 77.1% and 52.3%, at subject and implant level, respectively. Periimplantitis was diagnosed in 25 implants (12.7%) and 14 patients (29.2%). Success and survival rates were 82% and 97.6%, respectively. Our results suggest that subjects with osteoporosis and with full-mouth BOP scores ≥ 30% of the sites, as well as implants with visible plaque and sites with PD ≥ 4 mm, are more susceptible to peri-implantitis.